Effect of Vitamin E Supplementation on Copper and Zinc Levels in Plasma and Arsenic Level in Hair and Hoof of Arsenic Exposed Goats - Das, T. K.; Mani, V.; Kewalramani, N.; Kaur, H. (Indian Journal of Animal Nutrition, 2018)
The aim of the present experiment was to investigate effect of vitamin E supplementation on level of Cu and Zn in plasma and that of arsenic in hair and hoof in arsenic exposed goats. Twenty four crossbred lactating goats were randomly distributed into 4 groups of 6 animals each. All the animals including control group were fed basal ration to meet the requirement. The animals in groups T1, T2 and T3 were given arsenic @ 50 mg/kg DM while those in groupsT2 and T3 were additionally supplemented with vitamin E @100 IU and 150 IU/kg DM, respectively. The experiment lasted for 12 months. In all the groups, Zn decreased at the end of experiment while plasma Cu level was not affected. Plasma vitamin E level also decreased (P<0.05) in all treated groups and vitamin E supplementation in higher doses showed lower declining trend (12.23%) compared to its lower dose (14.05%). In all supplemented groups, plasma As level increased (P<0.05) and vitamin E in higher doses showed comparatively less increase in plasma As level. Concentration of As in hair and hoof increased (P<0.05) in all supplemented groups and vitamin E at higher doses reduced deposition of As. So, As exposure resulted in reduction in plasma Zn and plasma vitamin E level and increased retention of As in blood, hair and hoof in goats. Whereas, vitaminE supplementation @ 100-150 IU/kg DM reduced arsenic retention and resisted the decline in plasma Zn level.